Association between absolute lymphocyte count and overall mortality in patients with surgically resected gastric cancer - Se Jun Park; Jinsoo Lee; Hyunho Kim; Kabsoo Shin; MyungAh Lee; Jae Myung Park; Myung-Gyu Choi; Cho Hyun Park; Kyo Young Song; Han Hong Lee; In-Ho Kim (The Korean Journal of Internal Medicine, 2021)
Background/Aims Lymphocytes are an important component of the cell-mediated immune system. As lymphopenia is reportedly associated with poor prognoses in patients with various cancers, we investigated this notion in patients who underwent curative gastrectomy. Methods We retrospectively analyzed the association between absolute lymphocyte count (ALC) and prognosis in patients with stage I–III gastric cancer who underwent curative surgical resection. Ever lymphopenic patients were defined as those with ALCs < 1,000/μL at any time post-diagnosis except within 30 days post-surgery. Adjusted multivariable regression models were used to evaluate the associations between lymphopenia and overall mortality, gastric cancer-specific mortality, and disease-free survival. Results We investigated 1,222 patients diagnosed between January 2011 and December 2015. Fifty-six patients (4.6%) were lymphopenic at diagnosis and nearly one-quarter (24.8%) were ever lymphopenic with a mean minimum ALC of 640/μL. Older age (odds ratio [OR], 1.02) and higher stage (stage III vs. I; OR, 3.01) were positively associated with ever lymphopenia. On multivariable analysis, ever lymphopenia predicted higher overall mortality (hazard ratio [HR], 1.83; p = 0.008), higher gastric cancer-specific mortality (HR, 1.58; p = 0.048), and shorter disease-free survival (HR, 1.83; p = 0.006). The 5-year gastric cancer-specific mortality rates for ever- and never lymphopenic patients were 10.9% and 3.7%, respectively; their 5-year cumulative recurrence rates were 15.1% and 4.6%, respectively. Conclusions This study demonstrate that ever lymphopenia is independent prognostic factor for overall mortality and recurrence in patients with potentially curable gastric cancer; hence, ALCs may be a biomarker for predicting the prognoses of patients with stage I–III gastric cancer who had curative gastrectomy.